Prescribing pattern of clozapine and other antipsychotics for patients with first-episode psychosis: a cross-sectional survey of early intervention teams. Issue 3 (March 2017) - Tungaraza, Tongeji E.; Ahmed, Wakil; Chira, Chinonyelum; Turner, Erin; Mayaki, Susan; Nandhra, Harpal Singh; Edwards, Tom; Farooq, Saeed
Objective: To describe the pattern of antipsychotic drug prescribing in patients with first episode psychosis, with more emphasis in the use of clozapine in this group of patients. Method: A cross-sectional survey involving six early intervention service (EIS) teams in the West Midlands was conducted. Data was extracted from case notes and electronic records by clinicians working in each participating team. The pattern of antipsychotic prescribing and the changes that took place after being accepted in EIS, including the use of clozapine, was established. Clinicians involved in the treatment of patients in each team rated the overall clinical response to treatment based on the presence or absence of positive psychotic symptoms. Result: 431 patients with FEP were included in the final analysis. Low antipsychotic discontinuation rate was observed, with the majority (88.2%) still being prescribed antipsychotics. Most (77.3%) were prescribed second-generation antipsychotic drugs, with olanzapine (21.8%) and aripiprazole (19.7%) being the most frequently prescribed antipsychotics. There was low rate use of antipsychotic combinations (7.4%), high dose antipsychotic regime (3.9%), low depot antipsychotic prescribing (9.3%), and clozapine use was low (9.7%). On average, three antipsychotics were tried before clozapine was initiated and it took on average 19.5 months from being accepted into EIS to clozapine being initiated. Conclusion: The majority of patients were prescribed antipsychotics within the guidelines. EIS was associated with an overall low antipsychotic discontinuation. There was also a short waiting time before clozapine was initiated following patients being accepted into EIS.